Optimizing Tile Selection: Integrating Feasibility Evaluation in a Decision Support System using Analytical Hierarchy Process - Edward Joyce; Hsinchun Chen (IHSA Institute, 2023)
Tile selection in construction and design projects necessitates a holistic evaluation encompassing aesthetic, functional, and practical feasibility aspects. This research investigates and presents a Decision Support System (DSS) integrating the Analytical Hierarchy Process (AHP) with an innovative incorporation of feasibility evaluation for comprehensive tile selection. The research undertakes a systematic exploration of criteria paramount in tile selection, identifying durability, cost, aesthetics, and feasibility considerations as pivotal facets. The AHP methodology forms the backbone of the developed DSS, quantifying stakeholders' preferences, and weighing criteria to facilitate structured decision-making. A distinctive feature of the developed DSS lies in the seamless integration of feasibility evaluation. The system evaluates tiles not solely based on aesthetic appeal or functional attributes but encompasses practical aspects such as installation ease, maintenance requirements, and sustainability considerations. The effectiveness and efficiency of the DSS are highlighted through empirical application, showcasing its ability to streamline decision-making processes. The developed DSS emerges as a transformative tool, advocating for structured, informed, and sustainable decision-making in tile selection processes. Its potential impact spans industries, elevating standards and influencing best practices in decision-making across construction and design domains.